FAKTOR PENGARUH JANGKAUAN PELAYANAN FASILITAS UMUM NON-PEMERINTAH DI KAWASAN PERBATASAN (STUDI KASUS: KECAMATAN TEMPEL, KABUPATEN SLEMAN) - , TAUFIK HIDAYAT, Prof. Ir. Achmad Djunaedi, MUP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Region border is an imaginary line that separates two or politics or yurisdikasi such as countries, states or subnational regions. Attention to the border between the regions and the implications for economic growth tends to increase with the region as a function of resource limits. The economic opportunities arise because of the utilization of resources in both areas bordering and spatial proximity. In addition, increasing economic growth opportunities are affected by changes in the condition of the two countries towards cooperation tends to increase the potential for movement with the motive of economic opportunities (corporate or individual) because of the high market potential in accommodating a variety of resources owned by both regions. Border has an important role, because it determines the shape of an area, restricting the movement of people, including activities in the economic field. Generally the border is a barrier to immigration and imports of certain goods. Border between the two regions is determined by the relevant regional agreements and through some steps taken at the negotiating table to mark the border in actual field. Economic growth opportunities in frontier areas owned by the District Tempel. A district in Sleman district directly adjacent to the province of Central Java. District Tempel this sub region is not very extensive but no less crowded than trade areas in Yogyakarta and Central Java. Facilities and infrastructure of the city as a major supporter of the community life of urban infrastructure consisting of roads, electricity, etc. and facilities such as market infrastructure, schools, mosques, shops, etc. are incomplete at this district. Conditions of complete facilities and support as a community center in this District Tempel, making this district is always crowded during the busy time. People who come in and do the activity in this area, not only from DIY and this district alone, but from various regions outside the district administrative boundaries District Tempel and DIY come here, either for a visit or activity.